Pengembangan Bahan Ajar Matematika Berbasis STEM Pada Materi Bangun Ruang - Huswatun Hasanah; Sri Mukti Wirawati; Fitri Aida Sari (ILIN Institute Makassar, 2020)
The purpose of this research to develop teaching materials based on Science, Technology, Engineering, and Math (STEM). The type of research is Research and Development (R&D). Meanwhile, the teaching material is developed by ADDIE including five steps, namely analyze, design, development, implementation, and evaluation. The feasibility of the STEM teaching material refers to the results of three expert appraisals, namely education experts, STEM experts, and mathematics experts, then student responses. Student responses are used as testing subject were students of SMKN 2 Serang. The results showed that the teaching materials developed based on STEM was met the standard of feasibility aspects including validity, practicality, and effectiveness.